IMPORTANCE OF DEVELOPMENT LISTENING AND SPEAKING SKILLS THROUGH GAMES IN PRIMARY CLASSES - Oblayorova Muxlisa; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In this article, as a result of the use of modern approaches and innovative methods in teaching English in elementary grades, students develop logical thinking skills, fluency of speech, fluency of speech and develop the ability to respond correctly, arouse interest in knowledge, be thorough in lessons, communicate their desire to be ready.